The Benefits of Extensive Reading for Moroccan EFL University Students - Maryem Larhmaid (The Journal of Quality in Education)
This study examines the impact of an extensive reading program (Cycle Licence d’Education) on the vocabulary, reading comprehension, and critical thinking skills of 88 Moroccan English as a Foreign Language (EFL) students. Over 14 weeks, with 120-minute sessions weekly, participants engaged with texts from various fields such as history, philosophy, sociology, psychology, education, politics, religion, and science. Using a quantitative research design, pre- and post-assessments were conducted to measure the outcomes of the extensive reading module. Results showed a significant improvement in vocabulary, with two-thirds of participants (66%) reporting considerable progress in both vocabulary acquisition and its practical application. The program also positively affected reading comprehension, as 93% of students felt confident reading and understanding complex texts. Furthermore, 84% of students acknowledged that the program significantly enhanced their critical thinking abilities when engaging with academic materials. These findings provide valuable insights for EFL/ESL educators and curriculum designers, highlighting the importance of extensive reading programs in developing language skills and fostering critical engagement with academic and literary texts.